Theoretical and experimental investigation of the effects of Pr dopant on the electronic band structure, thermal, structural, in vitro biocompatibility of Er-based hydroxyapatites - Ahmed, Lana Omar; Bulut, Niyazi; Osmanlioglu, Fatih; Tatar, Beyhan; Kebiroglu, Hanifi; Ates, Tankut; Kaygili, Omer (Elsevier, 2023)
Pr and Er co-doped hydroxyapatites (HAps) have undergone their first theoretical and experimental re-search. Pr content was changed in 0.13 percent increments from 0.13 to 0.78 percent. Er content was kept constant at 0.39 at.%. Theoretical results demonstrated an increase in the density from 3.154 to 3.179 g cm -3, as well as steady decreases in the bandgap from 4.1739 to 4.0618 eV. X-ray diffraction (XRD) pat-terns point out that all the samples consist of the single phase of the HAp. The crystallinity decreased steadily with adding of Pr. Pr-content has a considerable impact on all the XRD-related parameters, ther-mal behavior and morphology. The cell viability was affected by the co-dopant content, and this value was found to be higher than 83% for all the samples. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Bandgap; X-ray diffraction; Spectroscopic analysis